Asatryan A., Fayvush G. Important Plant Areas Representing the Rare and Threatened Habitat Types of Armenia. – Yerevan, 2013. – 78 p. (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Asatryan A., Fayvush G. Important Plant Areas Representing the Rare and Threatened Habitat Types of Armenia. – Yerevan, 2013. – 78 p.